Septoplasty in Children. Issue 2 (March 2016) - Cingi, Cemal; Muluk, Nuray Bayar; Ulusoy, Seckin; Lopatin, Andrey; Sahin, Ethem; Passali, Desiderio; Bellussi, Luisa; Atilla, Huntürk; Hanci, Deniz; Altintoprak, Niyazi; Rusetski, Yuri; Sarafoleanu, Codrut; et al.
Objectives: Physicians have long had concerns about the potential harmful effects of pediatric septoplasties on the nasoseptal growth process because septal cartilage is important for the growth and development of the face. Methods: In this review article, pediatric septoplasty and its indications are discussed, together with a literature survey. In addition, overviews of development of the nasal skeleton from neonate to adult, nasal growth, and cartilaginous septum are presented. Important issues and comments on pediatric septoplasties are provided. Results: During septoplasty procedures, elevation of the mucoperichondrium unilaterally or bilaterally does not negatively affect growth of the face. Stabilization of the septum may be easier when mucosal elevation is performed unilaterally. The nasal floor mucosa should not be elevated so to avoid damage to the incisive nerves. Corrections and limited excisions may be done from the cartilaginous septum. Separation of the septal cartilage from the perpendicular plate, especially at the dorsal part, should not be performed because this area is important for the length and height of the nasal septum and nasal dorsum. Incisions or excisions should not be performed through the growing and supporting zones, especially at the sphenoethmoid dorsal zone. Conclusion: Ifthere are severe breathing problems related to the septal deviation, septoplasty should be performed. In the majority of cases, septal surgery may be conducted in 6-year-old children. However, if necessary, septal surgery may be performed in younger children and even at birth.